PEMENUHAN HAK-HAK KHUSUS NARAPIDANA WANITA DI LEMBAGA PEMASYARAKATAN KELAS IIB PEKANBARU - Azalia, Larissa Evita; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The legal protection of women prisoners in the correctional system legislation has not been set. Whereas some things should be well considered towards women prisoners. Therefore, the problem that arises is, how the legal protection of women prisoners in the legislation concerning prisons, and whether the implementation of such protection is in conformity with the correctional system. Issues which were examined in this study were: (1) whether the fulfillment of specific rights of women prisoners have been fulfilled? (2) what are the obstacles to the fulfillment of specific rights of women prisoners? (3) what efforts can be made to fulfill the specific rights of women prisoners?The obstacles encountered in fulfilling the specific rights of women prisoners at the Correctional Institution IIB class was the lack of attention from the government, because the government did not create an official law which was specifically arranged for women prisoners. Other obstacles encountered in the field were the lack of funds to support the fulfillment of human rights of prisoners, and the lack of facilities and infrastructure which supported for the implementation of the fulfillment of specific rights of women prisoners at the Correctional Institution Class IIB Pekanbaru.This research was a sociological law research that was supported by observational studies and interviews, and used the law as an approach to primary legal materials. Besides, it also used a secondary legal materials sourced from books, the draft legislation, material from the internet, as well as empirical research in the field was in prison Class II B Pekanbaru. Furthermore all data were analyzed descriptively.The efforts can be made by the government are issuing laws or official regulations for women prisoners, and providing sufficient funds to build infrastructure which is more adequate in the Penitentiary. The results of this study showed that in the legislation, especially in law No. 12 of 1995 concerning correctional system, turned out the problem of legal protection of women prisoners had not been set. Because in the law only mentioned prisoners, did not differentiate between men and women. Similarly, in the reality of women prisoners in Penitentiary Class IIB Pekanbaru, specific rights of women prisoners had not been fully implemented. Thus, in the future it is necessary to make specifically rules governing the placement of women prisoners and their area should be separated by child inmates.Keywords: Women Prisoners, Correctional System, the Rights of Prisoners